Electrochemical Reduction of Carbon Dioxide to 1‐Butanol on Oxide‐Derived Copper. Issue 47 (9th September 2020) - Ting, Louisa Rui Lin; García‐Muelas, Rodrigo; Martín, Antonio J.; Veenstra, Florentine L. P.; Chen, Stuart Tze‐Jin; Peng, Yujie; Per, Edwin Yu Xuan; Pablo‐García, Sergio; López, Núria; Pérez‐Ramírez, Javier; Yeo, Boon Siang
Abstract: The electroreduction of carbon dioxide using renewable electricity is an appealing strategy for the sustainable synthesis of chemicals and fuels. Extensive research has focused on the production of ethylene, ethanol and n ‐propanol, but more complex C4 molecules have been scarcely reported. Herein, we report the first direct electroreduction of CO2 to 1‐butanol in alkaline electrolyte on Cu gas diffusion electrodes (Faradaic efficiency=0.056 %, j 1‐Butanol =−0.080 mA cm −2 at −0.48 V vs. RHE) and elucidate its formation mechanism. Electrolysis of possible molecular intermediates, coupled with density functional theory, led us to propose that CO2 first electroreduces to acetaldehyde‐a key C2 intermediate to 1‐butanol. Acetaldehyde then undergoes a base‐catalyzed aldol condensation to give crotonaldehyde via electrochemical promotion by the catalyst surface. Crotonaldehyde is subsequently electroreduced to butanal, and then to 1‐butanol. In a broad context, our results point to the relevance of coupling chemical and electrochemical processes for the synthesis of higher molecular weight products from CO2 . Abstract : Carbon dioxide was electroreduced to 1‐butanol on oxide‐derived copper. The reaction mechanism was determined to proceed through a combination of electrochemical and chemical steps, some of which require contrasting conditions. This example highlights limitations in one‐pot synthesis and provides a case for utilizing independently optimized sequential reactors in a tandem system to build complex molecules from low molecular‐weight feedstocks.